The Protective Effects of Moisturizer Containing Potentilla anserina Extract in the Topical Treatment of Skin Damage Caused by Masks - Choi, Hyeong; Ha, Ji Hoon; Kang, Hee Cheol; Seo, Won Sang; Bin, Bum Ho (International Journal of Molecular Sciences, 2023)
The use of face masks during the COVID-19 pandemic resulted in significant societal changes, particularly for individuals with sensitive skin. To address this issue, the researchers explored traditional medicine and identified Potentilla anserina extract as a potential solution due to its anti-inflammatory and moisturizing effects. This research investigated how this extract influences skin hydration, barrier function, and itching. The findings revealed that the extract had a hydrating effect by elevating Aquaporin-3 (AQP3) expression. Additionally, the study demonstrated that the extract improved skin barrier function, with Filaggrin (FLG) expression being approximately three times higher (p < 0.001) in the Potentilla-anserina-extract-treated group compared to the control group and the genes associated with itching being reduced. In this process, we researched and developed HPβCD (hydroxypropyl-β-cyclodextrin)-Liposome containing Potentilla anserina extract, gradually and sustainably releasing the active components of the Potentilla anserina extract. During four weeks of clinical trials involving individuals wearing masks for over 6 h a day, a moisturizer containing Potentilla anserina extract demonstrated a notable reduction in skin redness. Hemoglobin values (A.U.), which serve as indicators of skin redness, showed decreases of 5.06% and 6.74% in the test area inside the mask after 2 and 4 weeks, respectively, compared to the baseline measurements. Additionally, the moisturizer containing Potentilla anserina extract notably decreased Trans Epidermal Water Loss (TEWL), with reductions of 5.23% and 9.13% observed in the test area inside the mask after 2 and 4 weeks, respectively. The moisturizer, especially in the test area treated with the extract-containing moisturizer, significantly enhanced skin hydration compared to the control group. The Corneometer values (A.U) exhibited notable increases of 11.51% and 15.14% in the test area inside the mask after 2 and 4 weeks, respectively. These discoveries emphasize the potential of Potentilla anserina extract and its utility in tackling skin issues caused by mask wearing, including enhancing moisture, fortifying the skin’s barrier, and alleviating itching. These results indicate that moisturizers incorporating specific ingredients provide greater benefits compared to conventional moisturizers.
Keywords: 2-Hydroxypropyl-beta-cyclodextrin; COVID-19; Humans; Masks; Pandemics; Potentilla; Pruritus; COVID-19; hydroxypropyl-β-cyclodextrin; liposome; mask; Potentilla anserina extract; redness; skin hydration; skin moisture; TEWL